Evolutionary Pathway Determines the Stoichiometric Response of Escherichia coli Adapted to High Temperature - Linzner, Krista A.; Kent, Alyssa G.; Martiny, Adam C. (Frontiers in Ecology and Evolution, 2018)
Microorganisms exhibit shifts in elemental stoichiometry in response to short-term temperature increases due to varying growth rate, biochemical reactions, and protein degradation. Yet, it is unknown how an organism’s elemental stoichiometry will respond to temperature change on evolutionary timescales. Here we ask how cellular elemental stoichiometry and physiology change in Escherichia coli that have adapted to high temperature over 2,000 generations compared to their low temperature adapted ancestor. Cell lines evolved to a temperature of 42.2°C via two, negatively epistatic adaptive pathways leading to mutations in either the RNA polymerase complex or the termination factor rho. Compared to the ancestor, high temperature adapted cell lines overall had 14% higher N:P ratios, but did not differ significantly in C:N or C:P. However, cell lines with mutations in the rho gene had 13% lower C:N and 34% higher N:P. Furthermore, the two adaptive strategies of the rho and RNA polymerase mutations varied significantly from one another, cell lines with the rho mutation had lower C:N, higher N:P and higher protein content compared to cell lines with the RNA polymerase mutation. Thus, specific adaptive pathways modulate the effect of temperature on the cellular elemental stoichiometry and may explain why the elemental composition of specific lineages is differentially affected by temperature changes.